2008
DOI: 10.3138/cmlr.64.3.429
|View full text |Cite
|
Sign up to set email alerts
|

L2 Learner Production and Processing of Collocation: A Multi-study Perspective

Abstract: This article presents a series of studies focusing on L2 production and processing of adjective-noun collocations (e.g., social services).In Study 1, 810 adjective-noun collocations were extracted from 31 essays written by Russian learners of English. About half of these collocations appeared frequently in the British National Corpus (BNC); one-quarter failed to appear in the BNC at all, while another quarter had a very low BNC frequency. Based on frequency data and mutual information (MI) scores, it was disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
177
3
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(205 citation statements)
references
References 30 publications
19
177
3
6
Order By: Relevance
“…Previous studies have found that even advanced learners made mistakes when producing collocations, and L1 transfer was also observed in their errors (Farghal & Obiedat, 1995;Nesselhauf, 2005). The research of Siyanova and Schmitt (2008) showed that "the underlying the intuitions and fluency with collocations of even advanced learners do not seem to match those of native speakers" (p. 429). Moreover, an investigation of reaction time by Yamashita and Jiang (2010) showed that "EFL leaners made more errors with and reacted more slowly to incongruent collocations than congruent collocations" (p. 647), but Wolter and Gyllstad (2013) found that "advanced learners are highly sensitive to frequency effects for L2 collocations" (p. 451).…”
Section: Collocationsmentioning
confidence: 99%
“…Previous studies have found that even advanced learners made mistakes when producing collocations, and L1 transfer was also observed in their errors (Farghal & Obiedat, 1995;Nesselhauf, 2005). The research of Siyanova and Schmitt (2008) showed that "the underlying the intuitions and fluency with collocations of even advanced learners do not seem to match those of native speakers" (p. 429). Moreover, an investigation of reaction time by Yamashita and Jiang (2010) showed that "EFL leaners made more errors with and reacted more slowly to incongruent collocations than congruent collocations" (p. 647), but Wolter and Gyllstad (2013) found that "advanced learners are highly sensitive to frequency effects for L2 collocations" (p. 451).…”
Section: Collocationsmentioning
confidence: 99%
“…Hoffman and Lehmann (2000), Siyanova and Schmitt(2008), and Adolphs andDurow (2004 as cited in Durant, 2008) have indicated the ISSN 2162-6952 2016 www.macrothink.org/jse 24 merits of explicitly and implicitly teaching collocations to L2 learners. They argued that the preferences for the application of explicit versus implicit mode of teaching collocations rely upon the context of learning and learners' tendency.…”
Section: Four Collocation Instructional Methodsmentioning
confidence: 99%
“…For him, the contextualised nature of collocations implies that implicit learning is the best approach to enhance its development. Similarly, Siyanova and Schmitt (2008) contradict Wray (2002) model by claiming that L2 learners have been found to be sensitive to the patterns of co-occurrence frequencies; in their study, learners who had spent the longest time in English-speaking environments were the only learners who successfully distinguished medium to high frequency combinations. Other studies (e.g., Durrant and Schmitt 2010), however, have used lab-based experiments to test learners' retention of collocations they were exposed to in a controlled input during a lab training session.…”
Section: Naturalistic Learningmentioning
confidence: 99%
“…Therefore, a clear shortcoming in previous classroom learning studies is that the majority were testing the product of learning without relating it to the nature of the input involved in that learning, and how it might have affected their learning product. A few other studies (e.g., Schmitt 2008;Siyanova and Schmitt 2008;Wray 2002) have given an account on how language knowledge might have been influenced by the nature of input. Wray (2002), for example, argued that adult L2 learners do not retain information about collocations they encounter in input, because their mature cognitive system and the nature of their learning situations push them towards a word-focused approach of learning She justified this by claiming that collocations can only be learnt if they are present in the input of language; and since there is no reason to believe that the learners' input has been simplified in regard to collocational content, the absence of collocations in the learners' output indicates that adult learners are incapable of learning collocations implicitly through exposure.…”
Section: Naturalistic Learningmentioning
confidence: 99%